Active Feedback Learning with Rich Feedback. - Yu, Hang.; Short, Elaine Schaertl. (Tufts University. Tisch Library., 2023)
Keywords: deep learning, human-robot interaction, interactive reinforcement learning, rich feedback.; Topic: Computing methodologies / Machine learning / Learning paradigms / Reinforcement learning; Topic: Computer systems organization / Embedded and cyber-physical systems / Robotics; ACM Open.